First results from an airborne GPS radio occultation system for atmospheric profiling. Issue 5 (5th March 2014) - Haase, J. S.; Murphy, B. J.; Muradyan, P.; Nievinski, F. G.; Larson, K. M.; Garrison, J. L.; Wang, K.‐N.
Abstract Global Positioning System (GPS) radio occultation (RO) from low Earth‐orbiting satellites has increased the quantity of high‐vertical resolution atmospheric profiles, especially over oceans, and has significantly improved global weather forecasting. A new system, the Global Navigation Satellite Systems Instrument System for Multistatic and Occultation Sensing (GISMOS), has been developed for RO sounding from aircraft. GISMOS also provides high‐vertical resolution profiles that are insensitive to clouds and precipitation, and in addition, provides greater control on the sampling location, useful for targeted regional studies. The feasibility of the system is demonstrated with a flight carried out during development of an Atlantic tropical storm. The data have been evaluated through a comparison with dropsonde data. The new airborne RO system will effectively increase by more than 50% the number of profiles available for studying the evolution of tropical storms during this campaign and could potentially be deployed on commercial aircraft in the future.